2015
DOI: 10.1124/jpet.115.223891
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Time-Dependent Changes in the Analgesic Effect of Pregabalin on Diabetic Neuropathy in Mice

Abstract: Patients with diabetes often develop peripheral nerve complications, including numbness and pain in the extremities. Diabetes-induced peripheral neuropathic pain is characterized by hypersensitivity to innocuous stimuli, known as tactile allodynia. Pregabalin (PGN) is currently used to treat diabetesinduced peripheral neuropathy and alleviates allodynia. In the present study, we demonstrated that the antiallodynic effect of PGN on diabetic mice was modulated by circadian changes in its intestinal absorption. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…application of 50 mg/kg pregabalin (equivalent to 314 μmol) was reported to yield a maximum analgesic effect for up to 1 hour, which was neutralized by 4 hours. 3 Here, we observed that a single dose of i.p. sivelestat at 20 mg/kg (equivalent to 46 μmol) completely reversed mechanical hypersensitivity in the STZ model for up to 6 hours.…”
Section: Discussionmentioning
confidence: 90%
“…application of 50 mg/kg pregabalin (equivalent to 314 μmol) was reported to yield a maximum analgesic effect for up to 1 hour, which was neutralized by 4 hours. 3 Here, we observed that a single dose of i.p. sivelestat at 20 mg/kg (equivalent to 46 μmol) completely reversed mechanical hypersensitivity in the STZ model for up to 6 hours.…”
Section: Discussionmentioning
confidence: 90%
“…Incubating the cells just with ERG showed that it was taken up about 100 times more quickly than was tetraethylammonium, leading to the designation of SLC22A4 as 'the' ERG transporter (130) . Subsequent work (87,(169)(170)(171)(172) has confirmed and reinforced this view of SLC22A4 and its homologues (173) as having significant specificity for ERG, and weak activity for various drugs (174)(175)(176)(177) . It is concentrative, coupled in humans to influx of 2 or 3 Na þ ions per ERG transported (130) .…”
Section: Slc22a4: the Ergothioneine Transportermentioning
confidence: 87%
“…It is concentrative, coupled in humans to influx of 2 or 3 Na þ ions per ERG transported (130) . Interestingly, it is up-regulated chronobiologically just before meal times (175) . The rat and human orthologues are interchangeable (178) .…”
Section: Slc22a4: the Ergothioneine Transportermentioning
confidence: 99%
“…It has been reported that organic cation transporter novel type 1 (OCTN1/SLC22A4) is a mediator of the intestinal absorption of pregabalin ( 31 ) and is expressed in hCMEC/D3 cells, at least at the mRNA level ( 27 ). In order to evaluate the contribution of OCTN1 to the pregabalin uptake by hCMEC/D3 cells, we utilized TEA at 1 mM, which reportedly inhibited OCTN1-mediated TEA uptake by 50–80% ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%